The Influence of Internal Factors on Going Concern Audit Opinions: Study of Industrial Companies on the Indonesia Stock Exchangee - Yolanda Zagoto, Akwilan Evalyn; Widiyati, Dian; Priyanto, Panji (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2024)
This research discusses the influence of independent commissioners, managerial ownership, and audit quality on accepting going-concern audit opinions. This research aims to determine the impact of independent commissioners, managerial ownership, and audit quality on the acceptance of going-concern audit opinions. The method used in this research is quantitative, and the data used is secondary data. The sampling technique was carried out using purposive sampling by considering specific criteria determined by the researcher. The population used in this research is industrial companies listed on the Indonesia Stock Exchange for the 2018-2022 period, data processing uses e-views 12 version. Based on the research results, it can be concluded that independent commissioner and managerial ownership variables influence the acceptance of going concern audit opinions. Meanwhile, audit quality does not affect the acceptance of going-concern audit opinions.